Literacy Level and Happiness Score Across Countries: A Secondary Data Correlation Study - Dwi Fitra Arreski; Fadhilah Ahmad Qaniah (PSYCHONESIA: JOURNAL OF PSYCHOLOGY, 2025)
The purpose of this study was to determine how strong and significant the correlation test between the variables of literacy ability and happiness ranking of each country statistically. In this regard, the literacy and reading ability assessment conducted by PISA in 2018 showed that Indonesia was ranked 74 out of 79 countries. Lack of reading skills can lead to un-favorable effects in the future. Especially regarding aspects of human development, human resources and mental well-being. Previously, there were several studies that attempted to examine the correlation between reading proficiency and well-being. However, no one has yet used widely available secondary data. In particular, the first is for reading assessment data from PISA and second, the Happiness World Report, both of which were conducted in 2018. This study uses a quantitative method with statistical analysis of the spearman correlation. Then, as additional information, the researchers also looked at the results of the simple regression or R2 statistical test. The results showed a positive and significant correlation between reading proficiency and happiness. With a correlation level or R value of .479** (p<.001) and an R2 adjustment value of 0.209**. Thus, the researchers concluded that reading proficiency from PISA proved to be correlated with each country's happiness ranking with moderate strength.